(untitled) (Fiep Bulletin - online, 2014)
The ventilator-associated pneumonia (VAP) is the infection acquired in the intensive care unit more frequent in patients requiring invasive mechanical ventilation (IMV), risk factors for VAP can be modifiable or not, can relate to the patient or treatment. Some measures to prevent VAP has been shown effective in reducing their occurrence being increasingly used in intensive care units (ICU). Aiming to verify if preventative measures interfere with the rate of VAP in an intensive care unit, oncology high complexity in western Paraná. To this end, we conducted a survey of a cohort of patients undergoing IMV, data collection was conducted by staff of the hospital and CCIH began in January 2010 extending until December 2012, being fragmented into two chronological time, before and after implementation of a protocol for the prevention of VAP. At the end of the study, we observed a decreased incidence of VAP, this value being 30.04 VAP cases/1000 days of VMI in 2010, before the implementation of the protocol and after the implementation of the protocol, in the years 2011 and 2012 the incidence was 17.66 cases of VAP/1000 days of IMV and 11.66 VAP cases/1000 days of IMV, respectively. We conclude therefore, that the adoption of preventive measures interferes with VAP, reducing their incidence as well as the risks attributed to it.